HUMAN VALUES IN THE INTERNATIONAL CRIMINAL COURT (ICC) - Ninepence, Albert Mcbell (Journal of Social Political Sciences, 2020)
The quintessence of the ICC in situ is that war crimes, terrorism, crimes against humanity and crimes of aggression are adjudicated effectively and equally. Countless individuals across the world have advocated justice to help curtail the hatred and nefarious actions plaguing marginalized and impacted communities. Therefore the ICC was founded in 2002 to foster justice and reconciliation for victims of abuse and crime. Regardless of the sudden recognition by the ICC of the authority to prosecute crimes, the ICC has recently drawn strong criticism. This paper contends that the ICC is consistent with all modes of humanitarian action in theory rather than in practice. The paper explored the relationship between right-based approaches, new humanitarianism and justice, Dunantist or other types. In addition, key factors such as legitimacy, reputation, reasonable aspirations and pacification through the ICC's justice have been highlighted as factors that combat the functional compatibility of the ICC with humanitarian action.